Brain abscess or meningeal myelomatosis? A case of Nocardia otitidiscaviarum in a post-transplant multiple myeloma patient - Zainulabid, Ummu Afeera; Cheong, Xiong Khee; Kori, Najma; Wan Hanafi, Hany Haqimi; Abdul Wahid, S. Fadilah; Basir, Ani Anisa; Zainudin, Affiza; Ramli, Ramliza; Periyasamy, Petrick (Elsevier, 2025)
Central nervous system (CNS) lesions in patients with multiple myeloma can present a significant diagnostic challenge, as they may represent either neoplastic processes, such as CNS myeloma (meningeal myelomatosis), or opportunistic infections. Nocardia spp. are rare but potentially life-threatening pathogens in immunocompromised individuals, capable of causing brain abscesses that mimic tumor lesions.